Wine-washing: colonization, normalization, and the geopolitics of terroir in the West Bank's settlements. (June 2015) - Handel, Ariel; Rand, Galit; Allegra, Marco
Terroir describes a set of special characteristics of a given place—geography, geology, climate, and human agricultural traditions—that incarnates in the unique taste of its products, usually wine. In contrast to modern perceptions of territory as an abstract legal–political entity, terroir invokes images of organic relations between people and a specific land with a unique 'character'. The paper will analyze the evolving discourse in the West Bank settlements in recent years, which shifts the emphasis from biblical history, ideology, and security—to tourism, vineries, and terroir. The argument will be that the usage of sophisticated wine language enables normalization of the Jewish settlements in the West Bank in a paradoxical way that is emphasizing their location and blurring it at the same time. While the concept of normalization is usually applied to the 'quality-oflife' urban settlements, our paper concentrates on the small and 'ideological' settlements, which are located in the densest Palestinian regions. By that, we wish to contribute to the growing research body on the West Bank settlements, as well as to the fields of geopolitics, colonial and postcolonial studies, and cultural geography.